A Needs-Based English Camp Handbook for EFL Boarding School Students Using 4-D Model - Husnaini; Abdul Muthalib (Universitas Islam Negeri Palopo, 2023)
This study aimed to develop a needs-based English Camp handbook for EFL boarding school students at Muhammadiyah Boarding School Palopo using the 4-D model. The study was conducted in response to the limited effectiveness of the previous English Camp materials, which were considered less practical, less structured, difficult to use, and insufficiently aligned with students’ learning needs. This research employed a Research and Development design by adapting the 4-D model consisting of Define, Design, Develop, and Disseminate. The participants were 15 students who joined the English Camp program. Data were collected through needs-analysis questionnaires, interviews, field observations, expert validation sheets, and students’ responses. The data were analyzed using qualitative descriptive analysis and percentage-based quantitative analysis. The needs analysis revealed that students needed materials that emphasized speaking practice, vocabulary enrichment, communicative expressions, familiar topics, interactive activities, and visually supported learning resources. Based on these findings, the handbook was developed into five units: Self-Introduction, Daily Routine, Asking and Giving Directions, Describing People, and My Family. Each unit consisted of vocabulary enrichment, useful expressions, main materials, basic grammar, and interactive tasks. The expert validation results showed that the material aspect reached 97.5%, the language aspect reached 97%, and the design and layout aspect reached 88.75%, indicating that the handbook was feasible for use. Students’ responses were also generally positive, as they considered the handbook attractive, understandable, relevant, and helpful for English Camp activities. Therefore, the developed handbook is suitable as a supporting learning medium to strengthen students’ speaking practice and vocabulary mastery in EFL boarding school contexts.